The spread of the introduced ascidians Ciona robusta Hoshino & Tokioka, 1967 and Rhodosoma turcicum (Savigny, 1816) in the southwestern Atlantic - Danielle Fernandes Barboza; Luis Felipe Skinner (Ocean and Coastal Research)
New records of the introduced solitary ascidians, Ciona robusta and Rhodosoma turcicum, have been added to the southwestern Atlantic Ocean, from Cabo Frio to Ilha Grande Bay, Brazil, in surveys conducted since 2009. Both species occurred on natural and artificial substrates, in predator-protected habitats, and regions close to harbors or other maritime activities. The distribution of Ciona robusta was related to water temperature, influenced by upwelling intensity and temperatures below 25ºC, while R. turcicum was not sensitive to the range of recorded water temperatures. The occurrence of both species on sites close to maritime terminals suggests vessels as potential vectors.